Investments in the efficient use of land resources and rational land use in agriculture - Balamirzoev Nazim; Isaeva Shamsiyat; Yangulbaeva Luiza (BIO Web of Conferences)
With a growing global population and climate change, efficient use of land resources is becoming key to ensuring food security and sustainable agricultural development. Some researchers believe that investments in agriculture and land management can lead to increased productivity, lower costs, and increased profitability for farmers and other agricultural sector participants. Sustainable land management helps conserve biodiversity, restore soil fertility and reduce the negative impact of agriculture on the natural environment, while investment in agriculture can help reduce poverty and improve the livelihoods of rural communities through job creation, increased income and access to food. The relevance of the research is that we are exploring the possibilities of using and implementing new technologies and innovations in agriculture, such as the use of digital technologies, smart land management systems and the use of biotechnologies to improve the efficiency of the agro-industrial sector.